2021
DOI: 10.1163/15507076-12340016
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Complexity Measures as Indices of Language Proficiency in Writing: Focus on Heritage Learners of Russian

Abstract: The concept of linguistic complexity, understood broadly as a range of basic and elaborate structures available and accessible to learners as evidenced in their production of speech and writing (Ortega, 2003), has featured prominently in second language development research since the inception of the field. The field of heritage language acquisition, however, has only recently begun to engage linguistic complexity as a comprehensive lens for studying heritage language development. The current study contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…For instance, when comparing intermediate and advanced heritage learners of Russian, Kisselev et al. (2021) found that the amalgam measure of subordination (i.e., counts of all types of subordinate clauses) did not statistically differentiate these two proficiency levels in the heritage learner corpus. The authors did find that specific types of subordinate structures correlated with proficiency levels—with gerund, participle, and relative clause ratios growing with proficiency, and infinitive clauses and adverbial clause modifiers decreasing in number with proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, when comparing intermediate and advanced heritage learners of Russian, Kisselev et al. (2021) found that the amalgam measure of subordination (i.e., counts of all types of subordinate clauses) did not statistically differentiate these two proficiency levels in the heritage learner corpus. The authors did find that specific types of subordinate structures correlated with proficiency levels—with gerund, participle, and relative clause ratios growing with proficiency, and infinitive clauses and adverbial clause modifiers decreasing in number with proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these arguments, we felt that the use of the ACTFL proficiency guidelines as a measure of proficiency was well warranted. Additionally, the ACTFL‐based proficiency assessments have been utilized in previous empirical research on L2 writing development in Russian (Henry, 1996; Kisselev & Alsufieva, 2017).…”
Section: Linguistic Complexitymentioning
confidence: 99%
See 3 more Smart Citations